2011
DOI: 10.4103/0974-777x.91068
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic syndrome in classic dengue fever

Abstract: A 24-year-old previously healthy girl presented with persistent fever, headache, and jaundice. Rapid-test anti-dengue virus IgM antibody was positive but anti-dengue IgG was nonreactive, which is suggestive of primary dengue infection. There was clinical deterioration during empiric antibiotic and symptomatic therapy. Bone marrow examination demonstrated the presence of hemophagocytosis. Diagnosis of dengue fever with virus-associated hemophagocytic syndrome was made according to the diagnostic criteria of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…Secondary dengue infection (two sequential infections by different serotypes) is also a risk for severe dengue. However, we and others [3,4,12,[16][17][18] observed that primary dengue infections were as much at risk of severe DHF and dengue associated IAHS. Primary dengue infection with serotype 1 or 3 and secondary infection with serotype 2 can lead to severe DHF [24].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Secondary dengue infection (two sequential infections by different serotypes) is also a risk for severe dengue. However, we and others [3,4,12,[16][17][18] observed that primary dengue infections were as much at risk of severe DHF and dengue associated IAHS. Primary dengue infection with serotype 1 or 3 and secondary infection with serotype 2 can lead to severe DHF [24].…”
Section: Discussionmentioning
confidence: 98%
“…Fourteen reports described favorable outcome after specific therapy with corticosteroids and/or IVIG with variable treatment regimes [1,3,4,7,9,[12][13][14][15][16][17][18][19]. There were a total of 61 patients, with 18 adults (range 16-46 years) and 43 pediatrics (range 50 days-15 years).…”
Section: Other Similar and Contrasting Cases In The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Severe dengue can clinically manifest as shock, severe bleeding, and hepatic, cardiac or neurologic dysfunction [1]. It has being recognized as a cause of secondary HLH/HPS in Southeast Asia, but overall worldwide incidence of dengue associated hemophagocytosis remains low [3,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Few cases have been reported in the English literature, and are mostly associated with severe dengue [6][7][8].…”
Section: Introductionmentioning
confidence: 99%